Pengaruh Ukuran Perusahaan, Laba/Rugi Operasi dan Kepemilikan Publik terhadap Audit Delay Studi pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Tahun 2016-2018 - Lilis Saidah Napisah; Vania Ramadhani (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2020)
The study aims to determine the factors that can affect the company. Some of these independent variable include company size, profit/loss operation and public ownership on audit delay. The sampling technique which is used to get the sample is purposive sampling. The sample in this study is 30 samples company of manufacturing sector which listed on the Indonesian Stock Exchange for 3 years from 2016 – 2018. In this research used secondary data with financial statements that have been published. This study uses a quantitative approach, descriptive and verification methods. While data analysis is which is used analysis multiple linear regressions. The results of this study indicate that simultaneously company size, profit/loss operation and public ownership have significant effect on audit delay. And partially profit/loss operation and public ownership has a significant effect on audit delay, while company size has no effect on audit delay.